DEMOGRAPHIC DISTRIBUTION, ETIOLOGICAL BACTERIAL SPECTRUM AND ANTIBACTERIAL TREATMENT OF PATIENTS WITH ODONTOGENIC ABSCESSES AND PHLEGMONS OF THE HEAD AND NECK - Yanko Yankov; Lyuben Stoev (Peytchinski Publishing, 2023)
Background: Odontogenic abscesses are the most common pathology in maxillofacial surgery. Their frequency is significantly higher in people with poor social status. Materials and methods: The study retrospectively included 81 patients with odontogenic abscesses and phlegmons of the head and neck, hospitalized and operated on as an emergency case. Incision wound secretion for microbiological examination and preparation of an antibiogram were taken from each of them as a standard routine procedure. Results and discussion: The most affected are young patients (till 44 years), followed by patients in middle age (45-59 years). The reason for this is that with age, teeth gradually fall out of the dentition of mature individuals, and with this, the possibility of the occurrence of odontogenic infections decreases. The lower jaw is more affected. A mixed resident microflora comprising more than one bacterial species is isolated in 62% of all patients. Gram-positive bacteria isolated in the samples of the studied patients were coagulase-negative staphylococci (Staphylococcus coagulase negative, CNS), Staphylococcus aureus, Streptococcus anginosus and Streptococcus viridans. Gram-negative bacteria were Escherichia coli, Enterobacter cloacae and Stenotrophomonas maltophilia. Obligate anaerobes were found in only one sample. The isolated fungi were Candida albicans and Candidanonalbicans. Conclusion: In the studied group of patients with odontogenic abscesses, Gram-positive bacteria In the studied group of patients with odontogenic abscesses, Gram-positive bacteria were 2.5 times more than Gram-negative. Single antibacterial therapy is preferable for patients with small-area odontogenic abscesses, while triple antibacterial therapy is recommended for large-area odontogenic abscesses and their phlegmonous forms.